Body Positive: Understanding and Improving Body Image in Science and Practice - Daniels, Elizabeth A.; Gillen, Meghan M.; Markey, Charlotte H. (Cambridge University Press, 2018)
What would it be like to feel good about your body? Does anyone really fully appreciate their body? If diverse body shapes and sizes were shown in the media, would this change your perception? While this book addresses all of these questions and more, it is not simply a standard scientific exploration of poor body image. Instead, it examines a new movement focused on understanding what it is that leads people to love, appreciate, take care of, and embrace their bodies. Featuring chapters written by leading, international experts in the science and practice of body image, Body Positive is a provocative and engaging look at how we feel about our physical selves in the twenty-first century - and how we can all come to feel better than we currently do.
Le texte The health at every size® paradigm, de Watkins, P., Clifford, D. et Souza, B. (2018), p.160-187, a été donné en lecture au cours LIT4700.
Keywords: approches et analyses; care; corps; cours; discipline; discours dominant; grossophobie; lit4700; premier cycle; psuchologie; ressource en ligne; santé; santé mentale; sciences humaines; systèmes d'oppressions; thématiques